2009
DOI: 10.1007/s00405-009-0967-y
|View full text |Cite
|
Sign up to set email alerts
|

Otosclerosis: an organ-specific inflammatory disease with sensorineural hearing loss

Abstract: Otosclerosis is an inflammatory disease associated with persistent measles virus (MV) infection of the otic capsule. The nature of sensorineural hearing loss (SNHL) related to otosclerosis can be due to the chronic TNF-alpha release from the foci. TNF-alpha enters the inner ear fluid spaces in histologically active stages of otosclerosis and may cause outer hair cell functional disorder and subsequent SNHL without morphological changes of the organ of Corti. On the contrary, non-otosclerotic stapes ankylosis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 24 publications
2
34
0
4
Order By: Relevance
“…The theory of virus etiology has been supported by many reports (4,8,(13)(14)(15)(16)(17)26). Recently, Sziklai et al showed that MV N mRNA could be detected in all of 160 otosclerotic stapes bones by using the RT-PCR method (39). Furthermore, Gantumur et al reported that MV N mRNA was detected in primary cells derived from stapes bones (8).…”
Section: Discussionmentioning
confidence: 97%
“…The theory of virus etiology has been supported by many reports (4,8,(13)(14)(15)(16)(17)26). Recently, Sziklai et al showed that MV N mRNA could be detected in all of 160 otosclerotic stapes bones by using the RT-PCR method (39). Furthermore, Gantumur et al reported that MV N mRNA was detected in primary cells derived from stapes bones (8).…”
Section: Discussionmentioning
confidence: 97%
“…2 They are similar to the bone resorption defects described in human otosclerosis, 8 a complex disease attributed to persistent measles virus infection as well as genetic factors. 29 Otosclerosis is morphologically characterized by proliferation of spongiotic bone with lacunae centered on capillaries and filled with osteoblasts, osteoclasts, and macrophages. 8 In MPS VII dogs, temporal bone lesions are similar and characterized by increased bone deposition (thickening), with the presence of confluent perivascular osteolytic spaces filled with osteoclasts and numerous vacuolated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic process of otosclerosis is characterized by an inflammatory lytic phase followed by abnormal bone remodeling, which leads to sclerosis at very specific sites of predilection [Arnold and Friedmann, 1988;Sziklai et al, 2009]. Histologically, the oval window is the most frequently affected area of this process, causing partial or total fixation of the stapes footplate.…”
Section: Introductionmentioning
confidence: 99%
“…This loss in BC hearing is worse than age-related hearing loss by itself [Topsakal et al, 2006]. Proteolytic enzymes (hydrolases) from bursting lysosomes in histiocytes as well as TNF-␣ from otospongiotic microfoci have been suspected of causing sensorineural hearing loss in otosclerosis when released into the perilymph [Bretlau et al, 1982;Causse et al, 1989;Causse and Chevance, 1978;Sziklai et al, 2009]. In rare cases, sensorineural hearing loss is induced by otosclerotic foci that penetrate the cochlear endosteum to grow into the scala tympani or vestibuli [Schuknecht, 1983].…”
Section: Introductionmentioning
confidence: 99%